A loose self-checking method based on FBG for axle counting sensor. Issue 1 (July 2020) - Zhang, Lu; Wang, Zhixin; Yan, Qiuji; Lin, Jinfeng; Wu, Chunxiao
Abstract: In order to improve the reliability and safety of the axle counting sensor, a loose self-checking method based on fiber Bragg grating (FBG) is proposed. FBG is used to detect the axial strain of the bolt which is a part of the axle counting sensor. It can effectively detect the installation condition of axle counting sensor. When the axle counting sensor is loose or fall off, the FBG wavelength will be lower than the set threshold value and an alarm signal will be sent. The experimental results show that the measured data of the loose self-checking device under different tightening torques are consistent with the simulation results. The artificial loosening test of the bolt is carried out, which proves that the method can be used to check the loose condition.